(3TQM GdTGajI aj GdJUQjas - (3GdLGHQOj, aNQ GdOjf, CMeO Hf GdMSf Hf jhSa, J (B746(3g` (B1346(3es
(3ChdgG (B:s
(3ChdgG(B: (3fMeOc jG ef HjOg GdNjQ hGdLhO (B... (3bhdg(B: (3GdJUQja Yde HCUhd JYQa HgG CMhGd CHfjI Gdcde GdJj djSJ HEYQGH deG cGf bhdg Yde TGedG ddebUhO hZjQ GdebUhO CQOag HeG jNQL Shi GdeMOhOs
(3BNQgG (B:s
(3BNQgG(B: (3aEfg jcJH GdjGFjjf ddeZGjQI GdePchQI hdFdG jdJHS (B.. (3eVGQY JQi, hCeG GdhUd aPcQfG Cf GdfXQ HYO Pdc aj TjFjf adeG aQZ ef GdChd hgh eG dGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B1: 111s
(3cTa GdXfhf, L (B2: 1021s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdUQas